The Effectiveness of Watching Movies Using English Subtitles in Teaching Vocabulary - Firmansyah, Imam; Irnanda, Septhia; Yoestara, Marisa (LPPM STIKI Malang, 2024)
This study assesses the effectiveness of using movies with English subtitles for teaching vocabulary. Experimental research refers to a method in which one explores variables for their causing effect through manipulation and observes the impact on another variable. The present study was conducted experimentally with SMPN 1 Peukan Bada grade VIII students. The study's sample consists of 57 students divided into two classes: one, VIII 5, as an experimental class in which the movies were shown with subtitles in English, and the other, VIII 7, as a control class where the movie was presented without subtitles. Data has been collected in the form of pre-and post-tests to measure the improvement in vocabulary acquisition by students. The average of pre-tests was 58 for the experimental and 56 for the control classes. It was observed that the experimental class had a steep increase in their vocabulary score as compared to the control class. The mean post-test score of the experimental class was 90 while the average of the control class climbed up to 76. Data were analyzed using both independent t-tests and paired t-tests to determine the significance of differences between the two groups by SPSS. The results of the statistical analysis indicated that there was indeed a significant difference between the two classes, with the p-value less than <0.001. Therefore, it would be proper to conclude that the use of English subtitles while watching movies effectively enhances vocabulary acquisition for students.